2015
DOI: 10.3389/fpls.2015.00773
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression profiling under heat and drought treatments of HSP70 gene family in soybean (Glycine max L.)

Abstract: Heat shock proteins (HSPs) perform a fundamental role in protecting plants against abiotic stresses. Previous studies have made great efforts in the functional analysis of individual family members, but there has not yet been an overall analysis or expression profiling of the HSP70 gene family in soybeans (Glycine max L.). In this study, an investigation of the soybean genome revealed 61 putative HSP70 genes, which were evaluated. These genes were classified into eight sub-families, denoted I–VIII, based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 67 publications
8
62
1
Order By: Relevance
“…HSPs reveal a specific role in protein folding (chaperone function) and protection of nascent proteins during their transport into specific organelles such as plastids and mitochondria . In addition play important roles in different kinds of environmental stress conditions, such as heat and drought, low, and high temperatures and salinity . Several studies demonstrated an increase of plant HSP under different stress conditions, indicating an enhanced need for protein protection under drought stress .…”
Section: Discussionmentioning
confidence: 99%
“…HSPs reveal a specific role in protein folding (chaperone function) and protection of nascent proteins during their transport into specific organelles such as plastids and mitochondria . In addition play important roles in different kinds of environmental stress conditions, such as heat and drought, low, and high temperatures and salinity . Several studies demonstrated an increase of plant HSP under different stress conditions, indicating an enhanced need for protein protection under drought stress .…”
Section: Discussionmentioning
confidence: 99%
“…It suggested the WGD duplication might be the main mechanism of AAT gene family expansion and functional diversity during evolution of soybean. This result consisted with some other gene families in soybean, such as GST supergene family (Liu et al, 2015 ), receptor-like protein kinase genes (Zhou et al, 2016 ), HSP70 genes (Zhang et al, 2015 ) in soybean, or AP2/ERF superfamily genes and 14-3-3 family genes in Medicago truncatula (Chen et al, 2001 ; Qin et al, 2016 ; Shu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 89%
“…The existence of signal molecules such as mitogen-activated protein kinases (MAPKs) and dehydration-responsive elements (DREs) that can switch on and off a battery of genes in response to heat stress has been reported (Sangwan et al, 2002;Kidokoro et al, 2015). Further, role of heat shock proteins in the maintenance of protein homeostasis within plants in response to heat stress also suggests the trait's monogenic nature (Zhang et al, 2015). The monogenic nature of a complex trait has also been reported for other abiotic stresses (i.e., drought tolerance in lentil) (Idrissi et al, 2016;Singh et al, 2016a).…”
Section: Molecular Mapping Of Heat Tolerancementioning
confidence: 99%